2017
DOI: 10.1167/tvst.6.3.18
|View full text |Cite
|
Sign up to set email alerts
|

Association between Corneal Biomechanical Properties with Ocular Response Analyzer and Also CorvisST Tonometry, and Glaucomatous Visual Field Severity

Abstract: PurposeTo investigate the association between corneal biomechanical properties measured with the Ocular Response Analyzer (ORA) and also CorvisST (CST) tonometry, and glaucomatous visual field (VF) severity.MethodsOne hundred forty-six eyes of 91 patients with primary open-angle glaucoma who performed Humphrey Field Analyzer 30-2 or 24-2 SITA-Standard, ORA, and CST within 180 days were included in this multicentral, observational cross-sectional study. The association between ORA parameters (corneal hysteresis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 52 publications
3
19
0
Order By: Relevance
“…CH is an established risk factor for glaucoma development and progression. [5][6][7][8][9][10] In the present study, the AUC of CH was 0.71 and was significantly higher than that of BGF. Our results suggested that BGF is not useful in diagnosing POAG in the current population, which may be due to the broader background of glaucoma patients (POAG, not only NTG) in contrast to the original study in which BGF were developed, 12 as discussed later.…”
Section: Discussionsupporting
confidence: 39%
“…CH is an established risk factor for glaucoma development and progression. [5][6][7][8][9][10] In the present study, the AUC of CH was 0.71 and was significantly higher than that of BGF. Our results suggested that BGF is not useful in diagnosing POAG in the current population, which may be due to the broader background of glaucoma patients (POAG, not only NTG) in contrast to the original study in which BGF were developed, 12 as discussed later.…”
Section: Discussionsupporting
confidence: 39%
“…Another previous study reported that the maximum deformation amplitude measured by CST was associated with the size of β-zone parapapillary atrophy,16 which has been reported to be associated with the development, severity, progression, and location of glaucoma 1720. Our recent studies also suggested that CST parameters were associated with the activity and prognosis of angioid streaks,21 and also the severity22 and progression23 of glaucoma. However, a different study reported no relationship between ORA-measured corneal hysteresis (CH) and β-zone parapapillary atrophy 24.…”
Section: Introductionsupporting
confidence: 53%
“…Further, Hong et al37 reported that rapid visual field (VF) progression was more likely to occur in patients with high IOPcc, low CH, and a large recorded difference between IOPcc and GAT IOP. CST is a relatively new noncontact tonometry, and we have shown glaucomatous VF progression38 and also severity39 can be even better analyzed using CST-derived parameters (bIOP was not analyzed, because of the older software used). Albeit with the high repeatability suggested in the current study, bIOP may be useful to assess the progression of glaucomatous visual field (VF) progression.…”
Section: Discussionmentioning
confidence: 99%